Artificial Intelligence and Challenges in Ayurveda Pharmaceutics: A Review (AYUSHDHARA, 2022)
Ayurveda, the science of life is utilized for maintenance of health since ancient time. The main objective was to prolong lifespan of human subjects and also to maintain and promote their positive health and the same is the motto of Ayurveda science. Pharmaceutical branch in Ayurveda with more than five thousand permutation and combinations are used in day today practice for treatment of different ailments. This traditional medical system with established history of many centuries is becoming one of the most popular sciences with safety and efficacy. With increase demand of Ayurveda medicine and acceptance of Ayurveda in the entire world, there is requirement of modernization and use of advance techniques in Ayurveda Pharmaceutics. Now a day’s newly progressed branch known as Artificial Intelligence (AI) can be used to meet increasing demands of Ayurveda medicines and to tackle challenges faced during drug manufacturing. AI can be used to combine engineering principles into the drug development to overcome challenges faced in Ayurveda Pharmaceutics. This can be achieved through applicability of AI in the various sectors of Ayurveda pharmaceutics. An attempt has been made in this article to analyze challenges with probable solutions by using Artificial Intelligence for global acceptance of Ayurveda.